2019
DOI: 10.4491/eer.2018.341
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of organic matter biodegradation and physico-chemical parameters variation during co-composting of lignocellulosic wastes with Trametes trogii inoculation

Abstract: Lignin complexity molecule makes its biodegradation difficult during lignocellulosic wastes composting. So, the improvement of its biodegradation has usually been considered as an objective. This study aimed to determine the impact of Trametes trogii inoculation on organic matter and particularly on lignin and cellulose during green wastes co-composting with olive mill waste water sludge and coffee grounds. Three types of heaps (H1, H2 and H3) were investigated during 180 d. H3 and H2 were inoculated at the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A lignocellulosic waste composting study determined the effect of Trametes trogii (white rot fungus), during different composting stages on the lignin and cellulose decomposition. Inoculations done at 0, 120 and 180 days showed that, lignin degradation paced maximum at the maturation phase for all the treatments (Fersi et al, 2019). Xi et al (2012), studied the effect of initial-stage, two-stage, and multi-stage inoculations on the composting efficiency of MSW, where process efficiency was maximum for multi-stage microbial inoculations.…”
Section: Microbial Additivesmentioning
confidence: 99%
“…A lignocellulosic waste composting study determined the effect of Trametes trogii (white rot fungus), during different composting stages on the lignin and cellulose decomposition. Inoculations done at 0, 120 and 180 days showed that, lignin degradation paced maximum at the maturation phase for all the treatments (Fersi et al, 2019). Xi et al (2012), studied the effect of initial-stage, two-stage, and multi-stage inoculations on the composting efficiency of MSW, where process efficiency was maximum for multi-stage microbial inoculations.…”
Section: Microbial Additivesmentioning
confidence: 99%
“…During the biodegradation process, the biota could release a certain amount of energy, generating heat and producing a slightly increase in the temperature [33].…”
Section: Monitoring Of the Chemical And Physico-chemical Parametersmentioning
confidence: 99%
“…(g) (h) (i) The temperature was slightly higher for CWW with respect to NCWW (21.8 ± 0 vs. 21.4 ± 0.5 °C, respectively) (Table S3). Because of its abundant organic substance tent, cellulose is a source of carbon and energy for a wide range of microorganisms During the biodegradation process, the biota could release a certain amount of en generating heat and producing a slightly increase in the temperature [33].…”
Section: Monitoring Of the Chemical And Physico-chemical Parametersmentioning
confidence: 99%
“…The lowest values of the rate constants of mineralization were noted during composting feedstock with lignocellulosic materials [11,12]. Therefore, some authors, to accelerate degradation of lignocellulosic, use inoculation, e.g., with fungi producing non-specific laccase [13]. Laccases enhance the efficiency of of phenolic and non-phenolic compounds including lignin.…”
Section: Temperature Profiles and Organic Matter Removalmentioning
confidence: 99%